2022
DOI: 10.3390/jof8020128
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Saccharomyces Yeast Co-Fermentation with Saccharomyces cerevisiae to Improve the Polyphenol and Volatile Aroma Compound Contents in Nanfeng Tangerine Wines

Abstract: This study attempted to improve the polyphenol and volatile aroma compound contents in Nanfeng tangerine wines using non-Saccharomyces yeast and Saccharomyces cerevisiae. The effects of fermentation with pure cultures of Candida ethanolica, Hanseniaspora guilliermondii and Hanseniaspora thailandica, as well as in sequential and mixed inoculations (1:1 or 1:100 ratio) with S. cerevisiae in Nanfeng tangerine wines were evaluated. C. ethanolica was found to produce the most polyphenols (138.78 mg/L) during pure f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
(117 reference statements)
2
21
1
Order By: Relevance
“…A similar accumulation of lactic acid was also reported in cider fermentation 11 . Previous studies have demonstrated that a certain level of concentration of lactic acid results in wines with a softer flavor and lower acidity, which has a positive effect on the mouthfeel perception of wine 7,22 . The maximum content of ascorbic acid was detected in SP, whereas a little of it was detected in another two fermented wines.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…A similar accumulation of lactic acid was also reported in cider fermentation 11 . Previous studies have demonstrated that a certain level of concentration of lactic acid results in wines with a softer flavor and lower acidity, which has a positive effect on the mouthfeel perception of wine 7,22 . The maximum content of ascorbic acid was detected in SP, whereas a little of it was detected in another two fermented wines.…”
Section: Resultssupporting
confidence: 81%
“…Among terpenes, the d ‐limonene, with a sweet mandarin scent, dominated in mandarin juice, which was converted completely after fermentation. As in the tangerine wines fermented by Xu et al ., 22 esters, higher alcohols and fatty acids were found to be the most abundant volatiles in our mandarin wines. In our case, ethyl caprylate, with the smell of pineapple, apple, and brandy, 14 was the most prominent ester in CP and SC, with 1736.35 and 1086.09 μg kg −1 , respectively, whereas isoamyl acetate, with the aroma of banana, pear, and apple, 7 was dominant in SP mandarin wines (353.25 μg/kg).…”
Section: Resultssupporting
confidence: 76%
“…In addition, W. anomalus was targeted to be used in alcohol reduction in fermented beverages. Furthermore, a low ethanol producing non- Saccharomyces yeast has been also targeted for use in the high level formation of aromatic compounds, such as esters, higher alcohols and fatty acids [ 44 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the control group ( Figure 1E ), the Y-401 group had significantly the highest polyphenol content (9.17 mg/ml) ( p < 0.001). Cellulases secreted by S. cerevisiae , pectinases help plants release bound and free polyphenols, increasing polyphenols in fermentation products ( Xu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%